1659 Health effects of pesticides: problems to solutions. (24th April 2018) - Colosio, Claudio; Laan, Gert van der; Denny, Hanifa
Abstract : Aim of special session: Main problems related to pesticide use and abuse in the world will be addressed, with a particular effort for identifying possible solutions. Pierluigi Cocco 3, Erik Jors 4, Angelo Moretto 5, Leslie London 6, El Yamani Mounia 7, Francesca Larese Filon 8, Susan Brumby 9, Claudio Colosio 1, Silvia Fustinoni 10, Hanifa Denny 2 1 Department of Health Sciences of the University of Milan and International Centre for Rural Health of the S. Paolo Hospital, Italy 2 Foundation Learning and Developing Occupational Health, Leusden, The Netherlands 3 Diponegoro University, Semarang, Indonesia 4 Department of Medical Sciences and Public Health, University of Cagliari, Cagliari, Italy 5 Department of Occupational and Environmental Health, Odense University Hospital, Odense, Denmark 6 Department of Biomedical and Clinical Sciences, University of Milan, Milan, Italy 7 School of Public Health and Family Medicine, University of Cape Town, Cape Town, South Africa 8 Santé publique France, Direction Santé Travail, St Maurice, France 9 Unit of Occupational Medicine, Dept. of Medical Sciences, University of Trieste. Trieste, Italy 10 National Centre for Farmer Health, Western District Health Service, Hamilton VIC, Australia